2020
DOI: 10.21203/rs.3.rs-94798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female Labor Force Participation under COVID-19 Pandemic:Evidence from the first round of the Uganda High-frequency Phone Survey on COVID-19

Abstract: The outbreak of the novel coronavirus that causes COVID-19 disease has taken the world by storm, given the containment measures better known as the Standard Operating Procedures (SOPs), including strict or mild lockdowns and social distancing measures. The impact of these aggregated measures have caused not only loss of lives but also financial, economic, social and even political unrest around the world and Uganda has not been spared either, given its weak economic and health care system (UBOS 2020). This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(3 reference statements)
1
3
0
Order By: Relevance
“…For example, ref. [21] supports the phenomenon in Uganda, ref. [12] advocates for South Africa, and [23] studies the case of Zimbabwe.…”
Section: (I) the Repercussions Due To Social Distancing Measuressupporting
confidence: 56%
See 2 more Smart Citations
“…For example, ref. [21] supports the phenomenon in Uganda, ref. [12] advocates for South Africa, and [23] studies the case of Zimbabwe.…”
Section: (I) the Repercussions Due To Social Distancing Measuressupporting
confidence: 56%
“…The COVID-19 pandemic has forced many African countries to take drastic measures to reduce its spread and impact. Among these measures, we distinguish measures of confinement, strict or light lockdowns, and social distancing measures [20][21][22][23]. These measures are unprecedented and are the subject of many case studies.…”
Section: (I) the Repercussions Due To Social Distancing Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from the Uganda High‐frequency Phone Survey on Covid‐19, conducted in June 2020, a study found that 45% of adult men and 49% of adult women did not work in the week preceding the survey, due to Covid‐19 restrictions (James et al, 2020 ). Additionally, a research team that was studying the economic status of households in 21 parishes from two rural districts in Western Uganda, prior to the Covid‐19 lockdown, conducted a follow‐up survey in May 2020 to establish the impact of the lockdown on economic outcomes and wellbeing (Mahmuda & Riley, 2021 ).…”
Section: Methodsmentioning
confidence: 99%